2020
DOI: 10.1097/ta.0000000000002583
|View full text |Cite
|
Sign up to set email alerts
|

The impact of frailty on posttraumatic outcomes in older trauma patients: A systematic review and meta-analysis

Abstract: BACKGROUND Frailty is a risk factor for mortality among the elderly. However, evidence from longitudinal studies linking trauma and frailty is fragmented, and a comprehensive analysis of the relationship between frailty and adverse outcomes is lacking. Therefore, we conducted a systematic review and meta-analysis to examine whether frailty is predictive of posttraumatic results including mortality, adverse discharge, complications, and readmission in trauma patients. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 43 publications
2
22
0
Order By: Relevance
“…In this multicentre prospective study, our findings confirmed that frailty is a predictor of prolonged LOS, falls, readmission, and even mortality in older patients, which was in line with other previous studies [25,32,33]. As a precondition of adverse clinical events in older patients, frailty can objectively reflect the chronic health problems and medical needs of older people.…”
Section: Discussionsupporting
confidence: 92%
“…In this multicentre prospective study, our findings confirmed that frailty is a predictor of prolonged LOS, falls, readmission, and even mortality in older patients, which was in line with other previous studies [25,32,33]. As a precondition of adverse clinical events in older patients, frailty can objectively reflect the chronic health problems and medical needs of older people.…”
Section: Discussionsupporting
confidence: 92%
“…Frailty as a predictor of mortality has widely been applied in different populations: community-dwelling older adults [29], nursing home residents [30], critically ill patients [31] and oncology patients [32], with HR values ranging from 1.8 to 3.39. A large number of evidencebased systematic reviews and meta-analyses found that frailty could be a predictive factor for adverse outcomes, including mortality [30], hospitalization [33], and readmission [34], which means that screening for frailty is very important in a clinical setting.…”
Section: Discussionmentioning
confidence: 99%
“…Even before the COVID-19 pandemic began, frailty was recognized as a predictive factor for adverse outcomes, such as mortality ( 61 ), hospitalizations ( 62 ), and readmission ( 63 ). Consequently, frailty was proposed as an important aspect of patient assessment early in the pandemic.…”
Section: Discussionmentioning
confidence: 99%